Interações entre população humana e sauim-de-coleira (Saguinus bicolor) no uso de recursos em quintais nos fragmentos florestais urbanos de Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2015)
The bare-faced tamarin (Saguinus bicolor) is endemic primate of the Manaus region and the main threats to your preservation are the destruction and fragmentation of the forest. The city of Manaus has numerous forest fragments where groups of S. bicolor may be living periods of interaction with the human population through the sharing of resources. The study aims to investigate the types of interactions between residents and sauins in backyards near urban forest fragments and what the implications of these interactions for conservation. In addition it has been identified the fruit species present in the backyards of residents that are also used by sauins as food. The study areas were seven forest fragments distributed along the city of Manaus: Mundo Novo, Castanheiras, Francisca Mendes, Parque Sumaúma, Novo Cidadão, Nova Cidade e Cidade Nova. The study was descriptive and exploratory and the information was obtained through the application of structured interviews. For definition of the types were considered four categories of behavior: perception, attitudes, pro-activism and cultivation, that showing the different ways to interact with the sauim. The interactions identified between human population and bare-faced tamarin were: cooperation (55%), affection (20%), neutrality (11%), domestication (8%) and competition (6%). The fruit species more frequently recorded in the backyards were: Musa sp (banana) 14,11%, Malpighia sp (acerola) 9,31%, Inga sp (ingá) 9,31%, Persea sp (abacate) 7,51% e Annarcadium sp (caju) 6,01% and 54% shared between human population and bare-face tamarin. In this context understand this relationship of human population and bare-face tamarin can be one of the steps for planning of environmental education programs, favoring coexistence between humans and primate reaching the management objectives and conservation of the specie in the green areas still remaining in the city.
Keywords: Etnoprimatologia; Fragmento florestal; Saguinus bicolor (sauim-de-coleira); CIÊNCIAS AGRÁRIAS